Characteristics of French Fries and Potato Chips in Aspect of Acrylamide Content—Methods of Reducing the Toxic Compound Content in Ready Potato Snacks - Agnieszka Tajner-Czopek; Agnieszka Kita; Elżbieta Rytel (Applied Sciences, 2021)
The reduction of toxic acrylamide content in potato snacks, i.e., French fries and potato chips, is necessary due to the adverse effects of this compound on the human body. Therefore, in the presented review paper, a detailed characterization of French fries and chips in terms of AA content and their organoleptic quality is included. Detailed information was also collected on the raw material and technological factors that affect the formation of acrylamide content, including methods and techniques affecting the reduction of the amount of this compound in potato snacks. The obligation to control the level of acrylamide in various food products (including fried potato snacks with a higher content of this compound), introduced in 2018, has mobilized manufacturers to seek solutions, while scientists conduct further intensive research on the possibility of reducing the level of AA or even eliminating its presence from products. Therefore, it is necessary to conduct such activities, especially, because potato French fries and potato chips are willingly consumed by younger and younger consumers.